Mercado GLS: como obter sucesso com o público de maior potencial da atualidade - Ruiz, Guilherme de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The current paper presents itself as a pioneer and innovative initiative of thinking communication applying it to a very specific target audience: the homosexual segment. In the course of this study, peculiar characteristics concerning the needs and aspirations of this group have been analyzed. Data confirm this segment has one of the most meaningful market potential nowadays. In view of this, it has been carried out a detailed analysis about a Brazilian company entrepreneurship which proposed itself to enter into connection with this target. Finally it is made available to the reader a guide containing the guidelines and all the appropriate practices by the time a company decides to encompass the gay segment

O presente trabalho apresenta-se como uma iniciativa pioneira e inovadora de pensar a comunicação voltada para um público-alvo bastante específico: o segmento homossexual. Ao decorrer deste estudo, são analisadas características peculiares que tangem às necessidades e anseios desse grupo. Dados comprovam que este é um dos segmentos de maior potencial de mercado da atualidade. Em virtude deste fato, é feita uma análise minuciosa sobre o empreendedorismo de uma organização brasileira que se propôs a relacionar-se com esse target. Por fim, é disponibilizado ao leitor um guia que reúne as diretrizes e todas as práticas adequadas quando uma organização decide atingir o segmento gay
Keywords: Homossexualismo; Comunicação em marketing; Mercado; Empreendedorismo